Sedentary Behaviour, Therapists, and Clients: Promoting Positive Health Behaviours in Therapy - Hawryliw, Stephanie T. (Canadian Journal of Counselling and Psychotherapy, 2017)
Sedentary behaviour is increasingly on the rise and has many negative health effects. This article provides a literature review on the health effects of sedentary behaviour and explores how this information is relevant to the field of counselling psychology. Additionally, it offers preliminary suggestions for how positive health behaviours regarding sedentary behaviour and movement may be promoted in therapy.